Middle ground approach to paradox: Within- and between-culture examination of the creative benefits of paradoxical frames - LEUNG, Angela K. Y. (Institutional Knowledge at Singapore Management University, 2018)
Thriving in increasingly complex and ambiguous environments requires creativity andthe capability to reconcile conflicting demands. Recent evidence with Western samplessuggested that paradoxical frames, or mental templates that encourage individuals torecognize and embrace contradictions, could produce creative benefits. We extendedthe timely, but understudied, topic by studying the nuances of for whom and whycreative advantages of paradoxical frames emerge. We suggest that people endorsinga middle ground approach are less likely to scrutinize conflict and reconcile withintegrative solutions, thus receiving less creative benefits of paradoxical frames. Fivestudies that examined individual and cultural differences in middle groundendorsement support our theory. Study 1 found that paradoxical frames increasedcreativity, but failed to replicate that experienced conflict mediated the relationship in aTaiwanese sample. In both within- and between-culture analysis, we showed that thecreative advantages of thinking paradoxically and experiencing conflict emergedamong individuals who endorse lower (vs. higher) levels of middle ground (Study 2)and among Israelis whose culture predominantly endorses middle ground strategyless, but not among Singaporeans whose culture endorses middle ground more (Study3). Study 4 further demonstrated the causal role of middle ground in theparadox—conflict—creativity link. To answer "why", Study 5 situationally inducedintegrative complex thinking that sets distinctions and forms syntheses amongcontradictory elements, and found that low endorsers of middle ground performedmore creatively when they engaged integrative complex thinking to cope withparadoxes. This program of studies offers important insights on harnessing paradoxicalexperiences to catalyze creativity.